2016
DOI: 10.5114/ceji.2016.58815
|View full text |Cite
|
Sign up to set email alerts
|

The effect of kynurenic acid on the synthesis of selected cytokines by murine splenocytes – in vitro and ex vivo studies

Abstract: Kynurenic acid (KYNA), a secondary product of the kynurenine pathway of tryptophan degradation, known mainly as an endogenous neuroprotectant, shows also immunotropic properties. Some quantities of KYNA are present in food and are effectively absorbed in the gastrointestinal tract. Since the spleen is an important target of dietary immunomodulators, the aim of the study was to determine the effect of exogenous KYNA on murine splenocytes. Splenocytes isolated from adult BALB/c mice were used in the study. First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 27 publications
1
18
0
1
Order By: Relevance
“…It can decrease leukocyte recruitment and production of proinflammatory cytokines in splenocytes in vitro. [25][26][27][28] Notably, there is evidence that it can also negatively regulate TNFα, IL-17, and IL-23. 13,14 A recent publication suggested that KYNA inhibited IL-10 in vitro, IDO1 deficiency was associated with increased IL-10 production, and IL-10 -/-IDO1 -/-mice demonstrated more severe colitis than IDO1 -/or IL10 -/-mice.…”
Section: Discussionmentioning
confidence: 99%
“…It can decrease leukocyte recruitment and production of proinflammatory cytokines in splenocytes in vitro. [25][26][27][28] Notably, there is evidence that it can also negatively regulate TNFα, IL-17, and IL-23. 13,14 A recent publication suggested that KYNA inhibited IL-10 in vitro, IDO1 deficiency was associated with increased IL-10 production, and IL-10 -/-IDO1 -/-mice demonstrated more severe colitis than IDO1 -/or IL10 -/-mice.…”
Section: Discussionmentioning
confidence: 99%
“…There are strong indications that the action of KYNA varies depending on whether inflammatory or homeostatic conditions are considered. Under homeostatic conditions, KYNA induced interleukin 6 (IL6) mRNA expression 2 h after treatment in the breast cancer cell line MCF-7 ( 27 ) and cytokine secretion (TNF, IL6, IL1β, and IL10) in primary murine splenocytes after 72 h ( 62 ). A further in vitro study indicated that KYNA may be an early mediator of leukocyte recruitment, acting by triggering the activation of neutrophils as well as the adhesion of monocytes to fibronectin and intercellular adhesion molecule 1 via β1-/β2 integrin ( 63 ).…”
Section: Immunomodulative Properties Of Kynamentioning
confidence: 99%
“…S1P acts as a signalling factor that regulates the trafficking of immune cells and T-lymphocyte differentiation among others [ 147 , 150 ]. PLP is also a co-factor in the production of kynurenine and kynurenic acid from tryptophan that have shown anti-inflammatory and immunomodulatory effects [ 147 , 151 ].…”
Section: Vitamins Of the B Groupmentioning
confidence: 99%